Errors in judging "offside" in association football: Test of the optical error versus the perceptual flash-lag hypothesis - Helsen, W. F.; Gilis, B.; Weston, M. (Journal of Sports Sciences, 2006)
The objective of this study was to analyse the correctness of the offside judgements of the assistant referees during the final round of the FIFA 2002 World Cup. We also contrasted two hypotheses to explain the errors in judging offside. The optical error hypothesis is based on an incorrect viewing angle, while the flash-lag hypothesis refers to perceptual errors associated with the flash-lag effect (i.e. a moving object is perceived as spatially leading its real position at a discrete instant signalled by a briefly flashed stimulus). Across all 64 matches, 337 offsides were analysed using digital video technology. The error percentage was 26.2%. During the first 15 min match period, there were significantly more errors (38.5%) than during any other 15 min interval. As predicted by the flash-lag effect, we observed many more flag errors (86.6%) than non-flag errors (13.4%). Unlike the predictions of the optical error hypothesis, there was no significant difference between the correct and incorrect decisions in terms of the positioning of the assistant referees relative to the offside line (0.81 and 0.77 m ahead, respectively). To reduce the typical errors in judging offside, alternative ways need to be considered to teach assistant referees to better deal with flash-lag effects.